CRISP: A JavaScript strategy for cloud application development - Sahu, Ayush (My University, 2016)
The application development in cloud is increasing day by day. Various strategies are being employed for providing service over cloud. There are organizations which develop native application and want to provide and access the service through cloud. Such organizations need cost effective methods to deploy their service as application in cloud environment. The traditional methodology involves writing efficient code in a language for a particular platform. This code provides high efficiency during execution while keeping the deployment cost low. But development time and development cost always increases when we follow such methodology. Also the code is not portable to be executed on other platform. Thus these complex methodologies of cloud development are not suitable for beginners, small organizations and startups as they have low budget and less experience to implement such methodologies. In this thesis, CRISP (Conversion, Reformat code, Isolate module, Sandbox, Partition) strategy has been proposed for refined conversion of native application to JavaScript for cloud application development. JavaScript is chosen as medium for writing application because it is mostly used language among developers and provides rich API (Application Programming Interface) for writing applications. It can be used both on client and server side hence it is easy to learn one language and implement services using it. However, hand written code and machine converted code are not efficient enough to be used for application development. If hand written code or machine converted code is used directly then it would lead to less efficiency and more development. The CRISP strategy allows to improve efficiency of code and optimize it for cloud application development. Various steps in this strategy removes bugs of converted code in each step. The code is divided into libraries to allowing code reuse for other applications. Finally the code is sandboxed to provide security and then it is hosted on cloud. The developed application can be deployed on cloud efficiently. Thus proposed strategy provides economic method for cloud application development.
Master of Engineering-Software Engineering
Keywords: Application Development in Cloud; Code Coversion; Sandboxing; Reformat Code